A study on the waiting time and processing time of green zone cases when triage by a doctor applied to edhusm - Mat Aripin, Azzuani (2014)
Introduction: In many countries, hospital Emergency Departments (ED) are experiencing problem associated with increased demand for their services. As a result, patient waiting times and overall processing time in the ED have increased beyond the acceptable level set by the government. In order to address the problems associated with this increased demand, numbers of projects were undertaken such as fast track approach, team triage, and mapping patient flow in ED. Thus, this study focused on effect of triage by doctor on waiting time and overall processing time and factors influencing the outcome. Objectives: Generally the objectives of this study were to determine the waiting time and processing time of green zone cases when triage by doctor applied to EDHUSM and to determine factors influencing outcome. Specifically, to study mean difference in waiting time and processing time between patient with triage by doctor and triage without doctor. Then, to study on factor influencing overall processing time and to determine association between patient’s satisfaction with the outcome. Methods: This prospective study was conducted in EDHUSM from 1st March 2013 to 30th April 2013, for only 6 hours a day. All green zone cases were included in this study. Exclusion criteria were all fast track patients (NNJ, psychiatry, Bronchial Asthma, OSCC), all yellow zone cases, and all red zone cases. Their time of registered, time of triaged, time seen by doctor and time of referred or discharged or admitted were monitored. Apart from that, every procedures including medications, radiograph, blood sampling, ECG, POCT were stated and ticked in the study form. Waiting time means the time they registered to the time they first seen by doctor with intervention. Processing time means time of registered to the time of discharged or referred or admitted. After overall processed, patient or their relatives were asked to fill up satisfactory feedback form. Results: There were total of 260 subjects (130 subjects each group) in this study. Waiting time and processing time among patient who have been triaged by doctor was significant with p<0.001 compared to patient triaged without doctor.No significant difference between trauma and non-trauma patient in terms of waiting time when triaged by doctors with p value = 0.238.The factors that influencing the processing times in both groups were treatment without doctor, number of procedures and weekdays (p<0.001). In multiple logistic regression analysis only three factors were found to have significant association with poor satisfaction when triaged by a doctor applied to EDHUSM. They were the duration of their illness (p = 0.004), prolonged waiting time (p<0.001) and longer processing time (p<0.001). Conclusion: We concluded that, triage by a doctor can shorten waiting time and improved the processing time by quick assessment and intervention. Indirectly, it will reduce overcrowding in emergency department. Hence, reduce complaints and dissatisfaction.